A Mother’s Account About Lactation in the Context of Perinatal Death (American International Journal of Humanities, Arts and Social Sciences, 2020)
Objective: To discuss the importance of listening and having a humanized intervention in regard to the donation of breastmilk in the context of perinatal death.Methodology: Content analysis of an interview with a mother in mourning that went through a traumatic lactation following a perinatal death. This case study is one of qualitative, longitudinal research, realized over two partially-structured interviews with parents who had lost their babies with less than 22 weeks of gestation at a public hospital, in Belo Horizonte, Brazil, from February to October 2019.Results: The interviews in the case of “Eva” (hypothetical name) presented significant suffering from lactation following the death of her child and her mourning process, which caught the authors’ attention about the importance of this topic.Conclusions: Women who have lost their babies before, during, or after birth should be offered the option of donating their breastmilk, to allow them to choose what to do with it, and then to counsel them during the mourning process.